Japan-Philippines Economic Partnership Agreement (JPEPA): Toward a Framework for Regional Economic Integration - Erlinda M. Medalla; Jenny D. Balboa; Catherine Vidar-Vale (Philippine Institute for Development Studies (PIDS), 2010)
With less than two years after its ratification, many of the economic gains expected under JPEPA have yet to be realized. But while critics may be quick to judge its failure due to this seeming lack of progress, neither have there been costs and dislocations that should have been more immediately evident. Moreover, the recent trends in trade and investments appear encouraging. Nonetheless, the implementation of JPEPA is wrought with challenges particularly those that involve undertaking internal reforms needed to realize its rich potential and achieve the vision upon which it was established. Being the first bilateral free trade agreement entered into by the Philippines, the performance of and experience with JPEPA are crucial in determining the prospects for negotiated trade agreements with the country. The Philippines cannot afford to slow down with the pace of reform and needs to march aggressively alongside its neighbors in East Asia, which is leading the move toward regional integration. This paper will revisit the seminal studies that examined the desirability of JPEPA with the aim of bringing to the fore the pending actions to generate the expected benefits from JPEPA.
Keywords: 330; Philippines; regionalism and bilateralism; economic partnership agreement; free trade agreements (FTAs); Handelsabkommen; Regionale Wirtschaftsintegration; Handelsliberalisierung; Japan; Philippinen